(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
The purpose of the paper is to explore the unique and distinctive charisma of the Kom Rem or Koms, who are relatively small group of tribes in Manipur, North East India. The present paper takes into account the six constituent tribes of the Kom Rem and its socio-political constraints during the last decades of ethnic upsurge in the state of Manipur. It extracts the traditional geo-political implications of the tribes ˜nuetral approach; and its peculiar features as a way to lessen ethnic conflicts of bigger tribes vis-a-vis inter-tribal feuds at their nearest geographical suburbs. The paper concludes, the orientations and practices of these tribes during the ethnic conflicts of the 1990s in Manipur were unique conventional practices hardly materialized by any mainstream society. Neutral in nature, it must be conceded that this perspective was developed as results of natural inter linkages of various perceptible traditions and the need for a common principle in defining relations between the Kom Rem tribe, its constituent groups and the other. It was also the result of a long standing and mythically rooted â€˜collective identity- the Kom Rem or Koms, which has mismatches the communal advances amongst various belligerents recently.